2003
DOI: 10.1016/s0092-8674(03)00075-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival of DNA Damage in Yeast Directly Depends on Increased dNTP Levels Allowed by Relaxed Feedback Inhibition of Ribonucleotide Reductase

Abstract: In eukaryotes, DNA damage elicits a multifaceted response that includes cell cycle arrest, transcriptional activation of DNA repair genes, and, in multicellular organisms, apoptosis. We demonstrate that in Saccharomyces cerevisiae, DNA damage leads to a 6- to 8-fold increase in dNTP levels. This increase is conferred by an unusual, relaxed dATP feedback inhibition of ribonucleotide reductase (RNR). Complete elimination of dATP feedback inhibition by mutation of the allosteric activity site in RNR results in 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
460
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(491 citation statements)
references
References 42 publications
21
460
4
1
Order By: Relevance
“…Mammalian cell response to DNA damage is somewhat ambiguous since neither logarithmically growing nor synchronized cells show accumulation of dNTP pools after DNA damage [12]. Our data are consistent with the idea that cells accumulate dNTPs in response to DNA damage as suggested by Chabes et al [11]. Although the DNA damage response and dNTP synthesis pathways of yeast and mammals have significant similarities, it is neither clear why mammalian cells do not show an increase in the sizes of their dNTP pools nor how they perform the repair process in the event of DNA damage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mammalian cell response to DNA damage is somewhat ambiguous since neither logarithmically growing nor synchronized cells show accumulation of dNTP pools after DNA damage [12]. Our data are consistent with the idea that cells accumulate dNTPs in response to DNA damage as suggested by Chabes et al [11]. Although the DNA damage response and dNTP synthesis pathways of yeast and mammals have significant similarities, it is neither clear why mammalian cells do not show an increase in the sizes of their dNTP pools nor how they perform the repair process in the event of DNA damage.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that cell survival after DNA damage is directly linked to elevated levels of dNTPs in yeast [11]. Mammalian cell response to DNA damage is somewhat ambiguous since neither logarithmically growing nor synchronized cells show accumulation of dNTP pools after DNA damage [12].…”
Section: Discussionmentioning
confidence: 99%
“…The second is feedback inhibition by dATP. Chabes et al have recently shown that S. cerevisiae RNR is 10 times less sensitive to dATP inhibition than the mouse or calf thymus RNRs, requiring 50 μM dATP (with 5 mM ATP present) to observe inhibition in vitro (23,60). In our crude cell assays described above, the dNTPs have been removed by the ammonium sulfate fractionation and the Sml1 levels are very low due to its low concentrations inside the cell and relatively high K D with α (∼0.4 M) (74).…”
Section: Specific Activity Measurements Suggest That Rnr Need Not Be mentioning
confidence: 99%
“…The replication checkpoint response slows S-phase progression, stabilizes stalled replication forks, and increases RNR complex activity (Santocanale and Diffley, 1998;Lopes et al, 2001;Tercero and Diffley, 2001;Chabes et al, 2003). Recent data demonstrate that stabilization of replication forks is the main checkpoint function needed for cell survival in the face of replication stress.…”
Section: Introductionmentioning
confidence: 99%